Shoreline changes at the regional scale in Tuktoyaktuk and the Mackenzie Delta, calculated using Landsat satellite imagery from 1985 to 2013 - Rachid Ramoul (10856055) (2014)
The Canadian Arctic has long been perceived by many as a vast area of barren and frozen land, sparsely populated, and of little importance to the country’s economic growth. However, today this is no longer the case. The changing environment and increased development in this region have led to numerous environmental ramifications, one of the most prominent being shoreline changes. The purpose of this study is to investigate the impacts climate change, natural mechanisms, and increased anthropogenic activity have had on the shoreline in the hamlet of Tuktoyaktuk in the Northwest Territories, and the surrounding Mackenzie Delta from 1985 to 2013 using Landsat satellite imagery. Shoreline changes are quantified and given a rate and directional vector over time in order to determine the predominant trends of erosion or deposition. The results of this investigation indicate that shoreline erosion is one of the leading mechanisms of shoreline change in this region.